External and Intrapsychic Factors Determining Unethical Behaviours and Controversial Practices in Science - Karina Ozga, Wioletta (International Journal of Psychosocial Rehabilitation, 2021)
From one side, investigators are expected to strive for reliability and trustworthiness in publishing scientific data; on the other, meeting the numerous research indicators of their professional work. In this article, various aspects of controversial practices concerning intentional skipping essential issues in a paper, hypothesizing after results, data improvement, and statistical and methodological tweaking are examined. The current paper proposes a holistic understanding of the causes of controversial practices that includes the constellation of external factors in the context of the intrapsychic functioning of scientists. This approach gives a deeper insight into unethical behaviour mechanisms through the prism of needs, values, and personality traits. Self-enhancement values, narcissism, Machiavellianism, and hubristic pride, as well as needs for competition, glory, success, self-esteem enhancement, and obsessive passion, may provide fertile ground for unethical behaviour in science.